Effects of CPAP on energy expenditure in obese obstructive sleep apnoea patients: A pilot study. Issue 6 (November 2015) - Shechter, Ari; Pham, Tiffany; Rising, Russell; St-Onge, Marie-Pierre
Summary: We conducted a placebo-controlled crossover pilot study investigating the effects of 2 mo of active and sham continuous positive airway pressure (CPAP) on energy expenditure (EE) via whole-room indirect calorimetry in three obese obstructive sleep apnoea (OSA) patients. Total 24-h (active: 2970 ± 254 kcal/d, sham: 2705 ± 217 kcal/d; p  = 0.015) and mean sleeping (active: 1.60 ± 0.20 kcal/min; sham: 1.47 ± 0.17 kcal/min; p  = 0.038) EE were significantly increased after active vs. sham CPAP. Findings suggest that CPAP may correct a hypoxia-related adaptive decrease in thermogenesis.